66‐4: Reactive Monomers Optimized for Fast Response Liquid Crystals with High Reliability. Issue 1 (25th September 2020) - Chena, Mei; Song, Qi; Wei, Hongquan; Chen, Xingwu; Tseng, Te-Jen; Hsieh, Chung-Ching; Xiao, Juncheng; Li, Dongze; Chen, Lixuan; Zhang, Xin; Meng, Hong
Abstract : The demand for fast response liquid crystals (LC) with high reliability for high performance liquid crystal displays (LCD) is increasingly urgent. In this work, the relationships between the conditions of the UV process and the reliability of fast response LC were investigated. By the application of novel reactive monomers (RM) with faster polymerization rate and longer reaction wavelength, a kind of fast response LC with high voltage holding ratio (VHR) and low ion concentration has been obtained. This work provides new insights for the improved reliability of fast response LC without electro‐optical performance loss.